On the Polysemy Of the Lithuanian Už. A Cognitive Perspective - Inesa Šeškauskienė; Eglė Žilinskaitė-Šinkūnienė (Baltic International Yearbook of Cognition, Logic and Communication, 2015)
Adhering to the principle of motivated polysemy, this paper sets out to demonstrate how the principle works in interpreting numerous senses of the Lithuanian preposition už ‘behind, beyond’. The present investigation relies on the cognitive linguistic framework employed, first of all, by Lakoff (1987), Langacker (1987), Talmy (2000), Tyler and Evans (2003), and Tyler (2012), who mainly worked on English, and such linguists as Tabakowska (2003, 2010) and Shakhova and Tyler (2010), who attempted to investigate inflecting languages, such as Polish and Russian. Based on such semantic principles as types of Figure and Ground, their relationship (geometric, functional, etc.), contextual clues and pattern of usage, etc., the present paper demonstrates that the polysemy of už used with two cases, Genitive and Accusative, is not an array of arbitrary senses, but rather a motivated network. It posits a central sense of už based on Figure located in the back region of Ground. All other senses, namely, those of function, control, obstacle, sequential location, hiding and covering, boundary or border, spatial distance, temporal distance, quality distance, replacement, retribution and remuneration, and benefactive, are directly or indirectly derived from the central sense.
Keywords: motivated polysemy; cognitive linguistics; linguistics; semantics; language; lithuanian language; semantic principles; figure; ground